Stem Cell Course in the Middle East: Science Diplomacy and International Collaborations During the Arab Spring - Sarkadi, Balazs (Humana Press Inc, 2011)
In April 2011, an international advanced course and workshop entitled “Frontiers in Human Pluripotent Stem Cells” and an International Congress on Fertility and Genetics (http://www.fertigen.com.jo/ConferenceDetails.aspx) was held in Amman Jordan hosted by the Jordanian Society of Fertility and Genetics under the auspices of the International Cell Research Organization (ICRO), a UNESCO associated NGO. The Congress President Dr. Zaid Kilani, with Dr. Abdel Latif Abu Khadra, President of the Jordanian society for Fertility and Genetics, Dr. Rana Dajani of the Hashemite University of Jordan, and their Organizing Committee proved to be an excellent organizers and dedicated physician-scientists and, focusing on fertility, genetics and stem cells in a wide range of advanced therapeutic applications. Brilliant course participants included trainees, scientists and clinicians from the Greater Middle East. The lectures and practical sessions, presented by internationally acknowledged scientists, included overviews of recent achievements in pluripotent stem cell research, emphasizing the role of both the embryonic (ES) and induced pluripotent stem (iPS) cells. A major emphasis was placed on the clinical achievements in germ cell and umbilical cord stem cell transplantation issues, and on the potential of fast and successful prenatal and pre-implantation molecular genetics diagnostics. The organization of the stem cell course in the Holy Land especially emphasized that issues of “eternal life” and “rejuvenation” are already at hand—at least in the pluripotent stem cell research field. In the lively atmosphere of the course about 60 participants had heated discussions on the possibility and ethics of advanced prenatal diagnostics, and on regulatory issues reflecting the need of separation of clinically effective versus unapproved, unwarranted stem cell treatments. An open discussion of many ethical issues, reflecting profound differences in religion and medical tradition in the different countries, made this course exceptionally interesting for both teachers and trainees.